Intelligence Report on the Banyang Clan, Mamfe Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1942)
This file contains colonial intelligence report on Banyang Clan, Mamfe Division, Cameroons Province
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies